2018
DOI: 10.1021/acs.jafc.7b04641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adaptive Neuroprotective Mechanisms of Sulforaphane and its Interconversion Product Erucin in in Vitro and in Vivo Models of Parkinson’s Disease

Abstract: Several studies suggest that an increase of glutathione (GSH) through activation of the transcriptional nuclear factor (erythroid-derived 2)-like 2 (Nrf2) in the dopaminergic neurons may be a promising neuroprotective strategy in Parkinson's disease (PD). Among Nrf2 activators, isothiocyanate sulforaphane (SFN), derived from precursor glucosinolate present in Brassica vegetables, has gained attention as a potential neuroprotective compound. Bioavailability studies also suggest the contribution of SFN metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Sulforaphane, an isothiocyanate hydrolyzed from glucoraphanin, has received the most attention. In addition, the enzymolytic ITCs from gluconapin and glucoerucin are 1-butene-4-isothiocyanat and erucin, which also presented anticancer effects in vitro and in vivo (Melchini and Traka, 2010;Morroni et al, 2018). In the present study, sulforaphane concentration accounted for 62.59% of total ITCs in broccoli sprouts.…”
Section: Discussionsupporting
confidence: 46%
“…Sulforaphane, an isothiocyanate hydrolyzed from glucoraphanin, has received the most attention. In addition, the enzymolytic ITCs from gluconapin and glucoerucin are 1-butene-4-isothiocyanat and erucin, which also presented anticancer effects in vitro and in vivo (Melchini and Traka, 2010;Morroni et al, 2018). In the present study, sulforaphane concentration accounted for 62.59% of total ITCs in broccoli sprouts.…”
Section: Discussionsupporting
confidence: 46%
“…The GSH levels were evaluated in SH-SY5Y cells as previously described [ 28 ]. SH-SY5Y cells were seeded in a black 96-well plate at 2 × 10 4 cells/well and incubated for 24 h at 37 °C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that carnosic acid (CA) exerts antioxidant effects through activation of Nrf2, the latter upregulating expression of some of endogenous antioxidants such as GPx, glutathione reductase (GR) [ 106 ]. Moreover, isothiocyanate sulforaphane (SFN), another Nrf2 activator, also displays neuroprotective effects in PD models [ 107 ]. All those studies suggest that Nrf2 is a pivotal mediator of cellular antioxidative stress system.…”
Section: Anti-ros With Compounds For the Therapeutics Of Pdmentioning
confidence: 99%